The impact of price hedging on subsidized insurance: Evidence from Canada. (13th September 2021) - Slade, Peter
Abstract: This article examines the effect of price hedging on publicly subsidized insurance. Theoretically, the effect of hedging is found to have an ambiguous effect on the incentive to purchase revenue insurance. A simulation is used to analyze the relationship between hedging and the Canadian AgriStability program in three regions in Saskatchewan. AgriStability is a margin insurance product, though in the simulation I hold input use constant, allowing the program to operate as if it were revenue insurance. Hedging is found to substantially reduce enrolment in AgriStability in each region. Furthermore, in some simulations the benefits that producers receive from AgriStability are smaller than the value of government subsidies. The results offer an explanation for low participation in AgriStability and show that the risk‐reducing effect of AgriStability is moderated by the ability of crop producers to hedge price risk through other means. Résumé: Cet article examine l'effet de la couverture des prix sur de l'assurance subventionnée par l'État. Théoriquement, l'effet de la couverture s'avère avoir un effet ambigu sur l'incitation à souscrire à une assurance‐revenu. Une simulation est utilisée pour analyser la relation entre la couverture et le programme canadien Agri‐stabilité dans trois régions de la Saskatchewan. Agri‐stabilité est un produit d'assurance sur marge, dans la simulation l'utilisation des intrants est maintenue constante, ce qui permet au programme de fonctionner comme s'il s'agissait d'une assurance des revenus. On constate que la couverture réduit considérablement les inscriptions à Agri‐stabilité dans chaque région. De plus, dans certaines simulations, les avantages que les producteurs reçoivent d'Agri‐stabilité sont inférieurs à la valeur des subventions gouvernementales. Les résultats offrent une explication de la faible participation à Agri‐stabilité et montrent que l'effet de réduction des risques d'Agri‐stabilité est modéré par la capacité des producteurs agricoles à couvrir le risque de prix par d'autres moyens.